Neo-R1000: A Fast And Efficient Compact Spectrograph For Emission Line Objects Study At Bosscha Observatory - Hakim L Malasan; Imanul Jihad; Robiatul Muztaba; Irham T Andika; Evaria Puspitaningrum; Akira Arai; Hideyo Kawakita; T Yamamuro (Institut Teknologi Bandung, 2016)
In 2015, the Institute Teknologi Bandung (ITB) signed a Memorandum of Understanding with Sangyou Kyoto University (KSU). One realization of collaboration between ITB and KSU is observational program of Novae using a compact spectrograph NEO-R1000 (Novae and Emission line Objects with Resolution of 1000). This spectrograph is mounted at the Celestron C-11 (F/10.0) reflector and supported by a Losmandy G-11 equatorial mounting inside the GAO-ITB sliding roof building, Bosscha observatory, Lembang. The unique configuration of this spectrograph is the employment of mirror collimator and camera lens with focal length ratio of 3:1. This makes it has high speed characteristics. A slit width of 6.5 μm (4.7” @ C-11 reflector ) is combined with a fixed transmission grating of 600 grooves/mm and equipped with a ST-8 XME CCD camera (9 μm per pixel, 1530 × 1024 pixels), resulting in a resolution of R≈ 1000 at a wavelength of 5800 Å with effective spectrum wavelength coverage Δl 4000-8000 Å. NEO-R1000 spectrograph has additional peripherals such as a Fe-Ne-Ar hollow cathode tube (HTC) which is used as a comparison source. We take flat-field spectrum by using an acrylic board and a halogen lamp. The main primary aim of this spectrograph is to observe the Classical Novae in the southern sky as part of Collaborative Spectroscopic Observations for the Detection of Molecules in Classical Novae. This spectrograph can also be used to observe other emission line objects such as Planetary Nebulae, Comets, P Cygni star type, WR stars and Be stars. In June 2015, this spectrograph was successfully used to observe Nova Sgr 2015 no 2. Further developments of this spectrograph includes constructing a rotator to be attached to the flange of telescope to ensure high flexibility in observation of extended objects. In the future, a fiber optic connecting output pupil with the entrance slit of the spectrograph will be deployed to improve observational effectivity while reducing the load of spectrograph on telescope.